PEMANFAATAN MEDIA AUDIO VISUAL UPIN & IPIN EPISODE EKOSISTEM DALAM MEMBANTU PEMAHAMAN PESERTA DIDIK KELAS VI SEKOLAH DASAR - Bintang Titania Putri Riyadi, Naila; Damayanti, Salfina; Amelia, Dea; Kurniawati, Wahyu; Al Husna, Anisya (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2025)
This study aims to determine the benefits of audio-visual media Upin and Ipin ecosystem episode in helping the understanding of 6th grade elementary school students. The sample in this study were 6th grade students as many as 5 students. The method used is using a qualitative approach descriptive method, with research data collection methods through pre-test and post-test. Students are given a spectacle in the form of Upin and Ipin audio-visual media about ecosystems that are in accordance with the learning subjects taken. Comparing the results of student research before and after giving the spectacle of Upin and Ipin audio-visual media on ecosystem episodes. The pre-test and post-test assessment leads to a basic understanding of the ecosystem which includes: 1) students are able to know the basic understanding of ecosystems, 2) students can distinguish inanimate objects and living objects, 3) students can identify the relationship between living and inanimate objects in the surrounding environment. Based on the results of the pre-test and post-test, it shows that the audio-visual media Upin and Ipin ecosystem episode has benefits in helping 6th grade elementary school students' understanding of basic knowledge of ecosystem material.